Formas imperativas em tirinhas de jornais publicadas na cidade de Uberaba nos séculos XX e XXI - Peluco, Larissa Campoi (2016)
This work had as main objective to investigate whether there is variation in the use of the imperative verb forms in strips of newspapers published in Uberaba in the twentieth and twenty-first. The use of imperative sentences of Brazilian Portuguese in spoken and written form indicates that this phenomenon is in process variation. Language studies already conducted, as Scherre (2004, 2005), Borges (2005) and Alves (2008), indicate that the use of the imperative departs from the standard norm, favoring switching between forms associated with the indicative or subjunctive. Based on these findings and in view that the language is heterogeneous and varies over time due to the influence of linguistic and extralinguistic factors observed if this alternation occurs in written Portuguese at Uberaba city in two synchronic moments in the first fifteen years of the twentieth and twenty-first centuries. The data were collected from newspapers Lavoura e Comércio and Jornal da Manhã, both from Uberaba. The results show that the cartoons published in the first fifteen years of the twentieth century favor the use of the imperative in the subjunctive form with a frequency of 85%, while the cartoons published in the first fifteen years of the twenty-first century favor the use of the imperative in the indicative with a frequency of 97%, confirming the hypothesis that the twentieth century favors the imperative associated with the subjunctive, while the twenty-first century favors the imperative associated with the indicative.